Resistance exercise-induced muscle fatigue is not accompanied by increased phosphorylation of ryanodine receptor 1 at serine 2843. - Daniel Jacko; Käthe Bersiner; Gerrit Friederichs; Patrick Ritter; Linnea Nirenberg; Jan Eisenbraun; Markus de Marées; Wilhelm Bloch; Sebastian Gehlert (PLoS ONE)
Skeletal muscle fatigue has been shown to be associated with hyperphosphorylation of the ryanodine receptor 1 at serine 2843 (pRyR1Ser2843), due to chronic overloading exercise. We investigated whether pRyR1Ser2843, is a mechanism relevant for muscle fatigue also under acute, in contrast to chronic, muscle loading. 24 male subjects (age: 24,8±3,8; height: 182,8±7,2 cm; weight: 82,5±9,9 kg) were evenly (n = 6) assigned to the following four different resistance exercise (RE) groups: hypertrophy- (HYP), strength endurance- (SE), maximum power- (MAX) at the subjects' 10, 25 and 3 repetition maximum, respectively, and low intensity (LI) RE with 70% of the 10 repetition maximum. Each group completed three different RE volumes (1 set, 5, and 10 sets). Muscle biopsies from the vastus lateralis were taken before and after exercise, analyzed for pRyR1Ser2843 and examined for association with RE-induced muscle fatigue which was determined as reduction in maximum isometric force (isoFmax) in the quadriceps femoris muscle also before and after exercise.The degree of RE-induced muscle fatigue was specific in terms of set volume as well as of RE mode. isoFmax was not reduced in any group after one set of RE. Five sets led to a significant reduction of isoFmax in HYP and SE but not in LI and MAX (p<0,05). Ten sets of RE, as compared to five sets, exclusively induced further muscle fatigue in LI. In terms of RE mode differences, isoFmax reduction was generally higher in HYP and SE than in MAX and Li after five and ten sets of RE (p<0,05). However, pRyR1Ser2843 did not show any significant regulation, regardless of exercise condition. We conclude that despite its relevance in reducing muscle contractility in chronic overloading, pRyR1Ser2843 does not reflect the degree of muscle fatigue exerted by acute hypertrophy-, strength endurance-, maximum power and low intensity-oriented exercise.